Ethnography of Communication: SPEAKING Analysis on Childbirth Services in Sa'dan, North Toraja - Weny Lestari (MOZAIK HUMANIORA, 2023)
This study aims to identify cultural communication gaps in three common childbirth speech events, namely  among the Toraja ethnic community in Sa'dan, North Toraja involving childbirth attendants and different locations, namely (1) childbirth attended by a midwife in a healthcare facility, (2) childbirth attended by a to'mappakianak (traditional birth attendant) at the mother's home, and (3) childbirth with collaborative efforts between a midwife and to'mappakianak in a healthcare facility. To pursue the aim of this study, SPEAKING analysis was used. The SPEAKING analysis (Scene/Setting-Participants-Ends-Act-Key-Instruments-Norms-Genre) is a framework in communication ethnography study developed by Dell Hymes to understand and analyse the society and culture of an ethnic group through communication processes. The results indicated that both midwives and to'mappakianak culturally shared the same goal of safely attending childbirth. However, within the context of different speech community's perspectives, the experiences and cultural nuances of participants, including childbirth attendants, mothers, and families, also conveyed different meanings. These differences could be positive or negative for the involved participants. This study could provide insights for policy of maternal and child health service providers to consider cultural and communication factors in health services for Toraja ethnics in Sa'dan, North Toraja. In short, competent childbirth attendants should be culturally communicative and adhere to safe motherhood principles.